Prevalence and Risk Factors of Fasciolosis in Bali Cattle in Ujung Loe Subdistrict, Bulukumba Regency (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2020)
This study aimed to determine the prevalence and risk factors of fasciolosis in Bali cattle in Ujung Loe District, Bulukumba Regency. A total of 157 Balinese cattle fecal samples were collected and selected proportionally from 13 villages in Ujung Loe Subdistrict, Bulukumba Regency. The fecal examination was carried out by the sedimentation method to detect the presence of Fasciola sp. eggs based on the morphology. Risk factors of fasciolosis such as animal age, management, cage condition, intermediate host control, and farmer knowledge were analyzed using Chi-square and Odds Ratio. The results of this study indicated that the prevalence of fasciolosis in Ujung Loe District, Bulukumba Regency was 4.4%. The results of the Chi-square analysis showed that age and management system had a relationship with the incidence of fasciolosis, while other factors were not related to fasciolosis.
Keywords: Fasciola sp.; Fasciolosis; Bali cattle